1996
DOI: 10.1007/s004360050170
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression and inhibition of inflammation in mice induced by a small Taenia solium RNA-peptide to implanted T. solium metacestodes

Abstract: Subcutaneous implantation of Taenia solium metacestodes in mice induces an inflammatory reaction made up mainly of neutrophils and eosinophils after 12 days. Administration of a small RNA-peptide (metacestode factor, MF) purified from T. solium metacestodes significantly reduces the inflammatory site in both size and composition, yielding a very low number of eosinophils. The metacestodes implanted in control mice were completely destroyed and their remnants were surrounded by an intense inflammation predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…We have reported that metacestodes of T. solium secrete in vitro a factor that depresses human and murine lymphocyte proliferation (Molinari et al 2000;Tato et al 1995). Also, this factor impairs the humoral and cellular responses to metacestode antigens and inhibits the inflammatory reaction around metacestodes implanted subcutaneously in mice (Tato et al 1996;Molinari et al 1998). Besides this, it inhibits IL-2, IFN-c, IL-4 and TNF-a synthesis in vitro and in ex vivo (Arechavaleta et al 1998).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We have reported that metacestodes of T. solium secrete in vitro a factor that depresses human and murine lymphocyte proliferation (Molinari et al 2000;Tato et al 1995). Also, this factor impairs the humoral and cellular responses to metacestode antigens and inhibits the inflammatory reaction around metacestodes implanted subcutaneously in mice (Tato et al 1996;Molinari et al 1998). Besides this, it inhibits IL-2, IFN-c, IL-4 and TNF-a synthesis in vitro and in ex vivo (Arechavaleta et al 1998).…”
Section: Discussionmentioning
confidence: 92%
“…Likewise, Arechavaleta et al (1998) reported that a factor released from T. solium metacestodes (MF) depresses T cell proliferative responses and cytokine production (IFN-c IL-2, IL-4 and TNF-a). This MF also impaired the inflammatory reaction on implanted T. solium metacestodes in mice (Tato et al 1996;Molinari et al 1998).…”
Section: Introductionmentioning
confidence: 91%
“…The stimulating effect of F2 on spleen cell proliferation and production of IFN-c has been reported (Garrido et al 2001). In addition, mice implanted with metacestodes showed inhibition of inflammation around the parasite and a decrease in the levels of antibodies and proliferative responses against parasite antigens (Tato et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, they induced a granulomatous process around metacestodes implanted subcutaneously that destroyed the parasite (Tato et al 1996;Molinari et al 1998). In all of these works, eosinophils (Th2 response) have been found in the inflammatory reactions surrounding the larvae and they have been related to the damage to the parasite.…”
Section: Discussionmentioning
confidence: 99%